Development of an accumulation assay and evaluation of the effects of efflux pump inhibitors on the retention of chlorhexidine digluconate in Pseudomonas aeruginosa and Staphylococcus aureus - Molly Mombeshora; Stanley Mukanganyama (BMC Research Notes, 2017)
Abstract Background Chlorhexidine digluconate (CHG) is used as a disinfectant. The emergence of pathogens resistant to the biocide raises health concern. Information on specific efflux mechanisms utilised by bacteria to confer reduced susceptibility to the biocide, may be used to develop ways of preventing the efflux of the biocide from nosocomial pathogens resulting in higher disinfection activity. The aim of the study was to evaluate the role of ATP-binding cassette transporters on the transport of CHG in bacteria. Methods Clinical strains of Pseudomonas aeruginosa, Staphylococcus aureus and their respective laboratory strains ATCC 27853 and ATCC 9144 were used for susceptibility tests. The minimum inhibitory concentration (MIC) of CHG with or without an efflux pump inhibitor [reserpine or carbonyl cyanide m-chlorophenylhydrazone (CCCP)] was determined using the broth microdilution method. A spectrophotometric method to quantify the amount of chlorhexidine in a sample was developed, validated and used to quantify CHG within P. aeruginosa and S. aureus cells. Results In the presence of reserpine, the MIC of CHG against the clinical strains of P. aeruginosa and S. aureus decreased from 6.3 to 3.2 µg/ml but showed no change against both ATCC isolates. The MIC of CHG in the presence of CCCP for both strains of P. aeruginosa remained unchanged but showed a reduction for both isolates of S. aureus. The suitability of the spectrophotometric method developed for quantifying the amount of CHG accumulated in microbial cells was validated and used successfully to quantify CHG accumulated within bacterial cells. Conclusion The spectrophotometric determination of CHG within microbial cells may be used to quantify CHG in microbial cells. Only the clinical strain of P. aeruginosa showed significant efflux of CHG suggesting the participation of efflux transporters in the pumping out of CHG from this isolate. The use of efflux pump inhibitors together with the biocide may be explored to preventing the efflux of the biocide from P. aeruginosa resulting in order to increase disinfection activity.